Causes and management of conflicts - Christoph Engel (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
In the social sciences and in the law, currently governance is the dominant perspective. Institutions are interpreted as governance tools. This view is helpful, but overly narrow. This paper adds conflict, and conflict management, to the picture. It provides a systematic overview of conceptual tools for understanding conflict, drawing on insights from economics, sociology and psychology. It also surveys competing normative views as to whether, and in which form, conflict is a good or a bad thing. Building on both, it looks at institutions reducing conflict risk, or managing conflict once it breaks out. The paper concludes with asking whether (also) adopting a conflict perspective might be how the law as a field is distinct from the (other) social sciences.
Keywords: 330